A Bibliometric Exploration of Sustainable Tourism Destinations: Trends, Perspectives, and Future Directions - Risda, Irfan Taufik (International Journal of Economics, Business and Innovation Research, 2025)
Sustainable tourism has become a focal point for governments, stakeholders, and academics, recognizing its role in promoting environmentally friendly and responsible development. The tourism industry, encompassing hotels, transportation, restaurants, and travel services, has made significant strides in adopting sustainable practices. However, comprehensive attention to destination management remains limited, largely due to the complexity of its elements. This study aims to systematically examine research on sustainable tourism destinations from 2012 to 2022 using Scopus data. A descriptive qualitative approach, combining bibliometric analysis and literature review, was employed. The study analyzed 200 international publications in English, sourced from the Scopus database with the keyword "sustainable tourism destinations." Findings indicate that the growth of Scopus-indexed publications peaked between 2018 and 2022, with 152 articles published. Notably, the journal Sustainability (Switzerland) frequently covers this topic, contributing 30 articles. Research trends were categorized into four major areas: research locations, approaches, scopes, and topics. Additionally, the study identified four primary perspectives in sustainable tourism destination research: social and cultural factors, business, economy and marketing, environment and ecology, and infrastructure and technology. A limitation of this study is its reliance on a single database, suggesting future research should incorporate broader literature sources. The findings provide valuable insights for academics and researchers focused on sustainable tourism destinations. KeyKeywords: Sustainable tourism, Destination, Bibliometric analysis.